2010
DOI: 10.1140/epjst/e2010-01243-x
|View full text |Cite
|
Sign up to set email alerts
|

Extreme events in optics: Challenges of the MANUREVA project

Abstract: In this contribution we describe and discuss a series of challenges and questions relating to understanding extreme wave phenomena in optics. Many aspects of these questions are being studied in the framework of the MANUREVA project: a multidisciplinary consortium aiming to carry out mathematical, numerical and experimental studies in this field. The central motivation of this work is the 2007 results from optical physics [D. Solli et al. Nature 450, 1054-1057] that showed how a fibre-optical system can genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…Following the pioneering work of Solli and coworkers [1] that have reported the observation of statistics analogous to hydrodynamic rogue waves in the formation of optical supercontinuum, most of the initial works have focused on the passive propagation of picosecond pulses in photonic crystal fibers [2]. Those different studies carried out in the anomalous dispersion regime have highlighted the specific role played by modulation instability, Akhmediev breathers [3,4] as well as Raman frequency shifted solitons that are also affected by third-order dispersion and resulting pulse-to-pulse interactions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Following the pioneering work of Solli and coworkers [1] that have reported the observation of statistics analogous to hydrodynamic rogue waves in the formation of optical supercontinuum, most of the initial works have focused on the passive propagation of picosecond pulses in photonic crystal fibers [2]. Those different studies carried out in the anomalous dispersion regime have highlighted the specific role played by modulation instability, Akhmediev breathers [3,4] as well as Raman frequency shifted solitons that are also affected by third-order dispersion and resulting pulse-to-pulse interactions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However a direct correspondence between nonlinear optics and hydrodynamics is provided by the one-dimensional nonlinear Schrödinger equation (1D-NLSE) (see Eq. (1)) that describes various wave systems [6,18]. In particular, the focusing 1D-NLSE describes at leading order the physics of deep-water wave trains and it plays a central role in the study of RW [6-8, 18, 19].…”
mentioning
confidence: 99%
“…Recently, it is demonstrated that the Peregrine rogue wave spectrum in the standard NLSE features a triangular shape and gets dramatically broadened at the maximally-compressed peak, which is corresponding to the onset of supercontinuum generation [27][28][29][30]. Thus, it is meaningful to study the spectral property of the transition between the Peregrine rogue wave and the w-shaped traveling wave.…”
mentioning
confidence: 99%